República Argentina, Océano Atlántico Sur, Islas Orcadas del Sur / compilación de levantamientos nacionales y extranjeros - Argentina. Ministerio de Marina (Argentina. Ministerio de Marina, 1952)
1a edición 1952 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines, bathymetric tints and soundings. 500 __ |a Includes tidal and conversion tables. 500 __ |a Selected lights shown in purple. 500 __ |a "I.B. de Etchepare Cartógrafo" -- lower right margin. "117." Color; 1:200,000